Comparative PMD Ensemble and Spectral Simulation of Fiber - Prof D. B. Bobade, Dr C. M. Jadhao (International Journal of Control and Automation, 2020)
The polarization-maintaining fiber designs presented are of dispersion-shifted, dispersion-flattened, and dispersion-unshifted types. The zero polarization-mode dispersion single-mode design is a dispersion-shifted fiber that provides large effective area and hence reduces signal distortions due to nonlinearity in fibers. The second order PMD is dependent of wavelength and it similar like chromatic dispersion and 2nd order coefficient is square of 1st order and the standard 2nd order PMD coefficient is less than or equal to 0.2 ps/nm Km. The proposed PMD coefficient for a 99.994% probability that the power penalty will be less than 1 dB for 0.1 of the bit period. The comparison is carried out and the PMD is created during fiber manufacturing, affected during cable manufacturing, installation and by the environment. Thus it is essential to measure PMD at every stage of the fiber life